Reversible splenial lesion syndrome in children: a retrospective study of 130 cases - Chen, Hui; Yu, Xiongying; Chen, Yong; Wu, Huaping; Wu, Zhuqiang; Zhong, Jianmin; Tang, Zhenyu (Frontiers in Neurology, 2023)
Background: Reversible splenial lesion syndrome (RESLES) is a new clinico-radiological syndrome. we retrospectively analyzed the clinical features of 130 children with RESLES in China, which is the largest case series available in the literature. Methods:The clinical data of children diagnosed as RESLES in Jiangxi Provincial Children's Hospital between 2017 and 2023 were retrospectively analyzed.. The 130 cases were divided into two groups: ≤3 years old group (group A) (n=83) and > 3 years old group (group B) (n=47). The Chi-Squared test or Fisher's test was used to evaluate the data. Results: The vast majority of patients (127/130cases, 97.7%) had prodromal symptoms of infection.Preceding infections of the gastrointestinal tract were statistically more significant in group A (60/83, 72.3%) than in group B (11/47, 23.4%) (P<0.05). Preceding infections of the respiratory tract were statistically more significant in group B (33/47, 70.2%) than in group A (17/83, 20.5%) (P<0.05). Seizures were statistically more significant in group A (82/83, 98.8%) than in group B (24/47,51.1%)(P<0.05). Disturbance of consciousness and headache/dizziness were statistically more significant in group B (27/47, 57.4%; 37/47, 78.7%) than in group A (3/83,3.6%; 1/83, 1.2%), respectively (P<0.05). Convulsions with mild gastroenteritis (CwG) were statistically more significant in group A (50/83, 60.2%) than in group B (8/47, 17.0%) (P<0.05). However, encephalitis/encephalopathy were statistically more significant in group B (20/47, 42.6%) than in group A (10/83, 12.0%) (P<0.05). MRI showed cytotoxic edema in typical locations (RESLES type-1 limited to the splenium of corpus callosum and RESLES type-2 spread to the entire corpus callosum, adjacent white matter, or both). There was full recovery of the lesions of MRI in all cases 3days-50days after the initial examinations. All the children showed normal neurodevelopment. Conclusions: Infection was the most common cause of RESLES. Infections of gastrointestinal tract is common in ≤3 years old children,while infections of respiratory tract is common in > 3 years old children.Younger patients are more likely to develop convulsions, and older children were more likely to have symptoms with disturbance of consciousness and headache/dizziness. RESLES has characteristic MRI manifestations and good prognosis.